How employees' perceptions of competency models affect job satisfaction? Mediating effect of social exchange - (:unkn) unknown (Allied Academies, 2016)
With growing emphasis being placed on human resource competencies as a means to be the indicator of employee potential to produce performance outcomes i.e. employee creativity and in turn organizational innovation, this study seeks to determine if competencies are predictive of employee behavior; determine if there is a relationship between competencies and job satisfaction of employees' perceptions; and determine the mediating effect of social exchange in this relationship. Analyses of 207 employees working in banking, telecommunications, health care, aeronautical and food industries in Turkey show that perceptions of competency model relevance and fairness has a positive effect on intrinsic and extrinsic job satisfaction. Also results show that social exchange partially mediated the relationship between perceptions of competency model relevance and fairness and intrinsic and extrinsic job.